2016
DOI: 10.1063/1.4953227
|View full text |Cite
|
Sign up to set email alerts
|

Concentric nano rings observed on Al-Cu-Fe microspheres

Abstract: It is well known that when particle size is reduced, surface effect becomes important. As a result, micro/nanoparticles tend to have well defined geometric shapes to reduce total surface energy, as opposed to the irregular shapes observed in most bulk materials. The surface of such micro/nanostructures are smooth. Any deviation from a smooth surface implies an increased surface energy which is not energetically favorable. Here, we report an observation of spherical particles in an alloy of Al65Cu20Fe15 nominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…1(a), which has been reported previously [2][3]. The new finding of the present work is shown in Figs.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…1(a), which has been reported previously [2][3]. The new finding of the present work is shown in Figs.…”
supporting
confidence: 90%
“…The feature of rings in Fig. 1(c) is in consistent with the typical concentric nanorings reported so far [3].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The alloy was prepared by arc melting pure aluminum, copper, and iron with a nominal atomic composition of Al 60 Cu 25 Fe 15 , the details of which are described in reference (Li et al, 2016). The prepared alloy appears to be porous and brittle.…”
Section: Methodsmentioning
confidence: 99%
“…The specimen used for testing is Al‐Cu‐Fe alloy (Li et al, 2016) and the particles of spherical shape found in it are of interest for this study. While the particles have complicated structures and phases, it is justified to consider them as single crystals of cubic structure since only the surface is of interest in this study.…”
Section: Introductionmentioning
confidence: 99%